Strategi Pengembangan Usaha Pengolahan Ikan Kering Di Kota Bengkulu - Destiana Rosifa; Reswita Reswita; Reflis Reflis; Valeriana Darwis (Universitas Mataram, 2026)
This study aims to identify internal and external factors, map the strategic position, and formulate and prioritize development strategies for the dried fish processing business in Bengkulu City. The method used is descriptive quantitative analysis with IFE and EFE matrix approaches, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM). Respondents totaled 16 people selected through purposive sampling, including business actors, fisheries agencies, cooperative and MSME offices, and consumers. The results show that the dominant internal factor is the business actor's experience (score 5.67) and raw material quality (score 5.50), while the main weakness is limited access to capital (score 3.00). Total IFE score of 4.72 and EFE of 3.79 placed the business in Quadrant I of the SWOT diagram (coordinates 2.76; 1.09), indicating an aggressive position. Based on QSPM analysis, the top priority strategy is developing product variety based on local experience (TAS = 5.79), followed by utilizing government assistance for production equipment modernization (TAS = 5.54), increasing production volume and market expansion (TAS = 5.25), government partnership (TAS = 5.22), and improving product quality for market penetration (TAS = 5.04).